Pelatihan Pemanfaatan Daun Kelor Sebagai Makanan Ringan Dalam Meningkatkan Pendapatan Masyarakat Kelurahan Panggi Kota Bima - Ismunandar Ismunandar; Mulyadin Mulyadin; Azwar Triyadi (Asosiasi Dosen Akuntansi Indonesia, 2021)
This community service activity aims to provide training on how toprocessing Moringa leaves into snacks and increasing public knowledge about business opportunities that can produce the basic ingredients of Moringa leaves. In the implementation of community service, there are several steps or forms of activities that will be carried out, including seminars and practice methods. In this community service, targets that are considered strategic to be involved in community service are people who mostly have Moringa plants and are interested in using the Moringa plant. Business from Moringa leaves has good prospects because the Bima City area has a lot of Moringa plants that can grow by themselves. In addition, most of the people of Bima City are aware of the benefits and nutritional value contained in Moringa leaves. If the business of utilizing Moringa leaves as a light raw material can be developed, it will have an effect on improving the economy of the people living in Panggi, Bima City.